Predation on livestock and its influence on tolerance toward pumas in agroecosystems of the Argentine Dry Chaco. Issue 5 (3rd September 2021) - Nanni, Ana Sofía; Teel, Tara; Lucherini, Mauro
ABSTRACT: As an apex predator, pumas ( Puma concolor ) frequently enter into conflict with humans because of predation on livestock. We analyzed the association between puma predation and human tolerance in six agroecosystems of the Argentine Dry Chaco, a global deforestation hotspot. Specifically, we addressed attitudes and behaviors of local social actors toward pumas, their association to reported livestock predation, and the incidence of livestock management and puma abundance on predation on livestock. Puma predation on livestock was considered an important cause of livestock loss. Attitudes toward pumas were negative, but were not strongly associated with predation. However, retaliatory hunting was more common among respondents who experienced livestock predation. Breeding goats and sheep and the lack of corrals increased livestock predation probability, which decreased with low puma abundance. Tolerance toward pumas is low in agroecosystems of this region, and further qualitative studies should address its likely hidden causes.